2002
DOI: 10.1006/brln.2001.2529
|View full text |Cite
|
Sign up to set email alerts
|

The Selection of Grammatical Features in Word Production: The Case of Plural Nouns in German

Abstract: Two experiments investigate the effect of number congruency using picture-word interference. Native German participants were required to name pictures of single objects (Nase 'nose') or two instances of the same object (Nasen 'noses') while ignoring simultaneously presented distractor words. Distractor words either had the same number or were different in number. In addition, the type of plural formation (same or different inflectional plural suffix) and the semantic relationship (same or different semantic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Since plural targets also require the determiner die, there would never be a mismatch in the plural. Earlier evidence on the selection of number features (Schiller & Caramazza, 2002) supports this latter view.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Since plural targets also require the determiner die, there would never be a mismatch in the plural. Earlier evidence on the selection of number features (Schiller & Caramazza, 2002) supports this latter view.…”
Section: Discussionmentioning
confidence: 84%
“…How can this difference in results be accounted for? One reason may be that gender agreement for adjectives, but not for determiners, involves the affixation of a bound 7 Previous experiments (Schiller & Caramazza, 2002) revealed that this effect is probably due to the fact that the distractor word interferes visually more with the presentation of a single picture (i.e., in the singular condition) than with the presentation of two identical pictures of the same object (i.e., in the plural condition). Except for Exp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with data from the picture-word interference paradigm. Schiller and Caramazza (2002) found semantic interference for semantically related pictures and words, but no effect of mismatching number. Similarly, our results showed similar speech onsets for the number matching condition (m = 843 ms; SD = 225 ms), and the mismatching condition (m = 822 ms; SD = 208), as well as similar gaze durations for the matching condition (m = 672 ms; SD = 242 ms), and the mismatching condition (m = 662 ms; SD = 221 ms).…”
Section: Discussionmentioning
confidence: 84%